Gestión de talento humano y su repercusión en la productividad de los trabajadores agrícolas de la empresa reybanpac cl. zona vergel cantón Quevedo, año 2023. - Valero Vera, Gabriel Lenin (2025)
Human talent management in the agricultural sector focuses on hiring, training, caring for, and motivating workers. Its proper application improves productivity, creates a positive work environment, offers training, values work, and fosters emotional well- being, all in order to increase performance, reduce staff turnover, and improve the quality of agricultural work. The main objective was to analyze human talent management and its influence on the productivity of agricultural workers at REYBANPAC CL, in the Vergel Zone of Quevedo, in 2023. The research was non-experimental, with a cross- sectional, descriptive, and correlational design. The sample of the study population consisted of 256 agricultural workers from the El Vergel Zone. For the analysis, a finite sample formula was used. The technique employed consisted of interviews with the manager and surveys with workers, using a closed questionnaire that addressed the variable of human talent management, as well as labor productivity. As a result, it was found that workers perceive a good level of both human talent management (54%) and labor productivity (74%). Furthermore, it was determined that there is a direct and significant relationship between working time, working conditions, efficiency and effectiveness, and the variable of human talent management. Finally, an intervention proposal was presented, including the identification of four strategies in human talent management to improve the productivity of agricultural workers. Training workshops were held that addressed various aspects, such as general knowledge about the company's productivity, motivation, teamwork, and, finally, an incentive program. .